Prebiotic Colloidal Oat Supports the Growth of Cutaneous Commensal Bacteria Including S. epidermidis and Enhances the Production of Lactic Acid - Liu-Walsh F; Tierney NK; Hauschild J; Rush AK; Masucci J; Leo GC; Capone KA (Dove Medical Press, 2021)
Fang Liu-Walsh,1 Neena K Tierney,1 James Hauschild,2 Allison K Rush,1 John Masucci,3 Gregory C Leo,3 Kimberly A Capone1 1Johnson & Johnson Consumer Inc., Skillman, NJ, USA; 2Johnson & Johnson Microbiological Quality & Sterility Assurance, Johnson & Johnson Inc., Raritan, NJ, USA; 3Janssen R&D Companies of Johnson & Johnson, Springhouse, PA, USACorrespondence: Fang Liu-Walsh; Kimberly A CaponeJohnson & Johnson Consumer Inc., 199 Grandview Road, Skillman, NJ 08558-9418, USAEmail fliuwals@ITS.JNJ.com; KCapone@its.jnj.comBackground: Multiple skin conditions have been associated with alterations in the diversity and composition of the skin microbiome, including dry skin and atopic dermatitis. In these conditions, a number of commensal skin bacteria have been implicated in supporting a healthy skin barrier, including Staphylococcus epidermidis. Recent clinical studies in patients with mild-to-moderate atopic dermatitis and dry/itchy skin have shown significantly improved skin barrier function and microbial diversity upon treatment with moisturizers containing 1% colloidal oat. We hypothesized that direct use of colloidal oat by skin microbes contributes to these therapeutic benefits.Methods: Skin bacterial growth was assessed using the BacT/ALERT system. Staphylococcus aureus and S. epidermidis growth rates and metabolism were compared in an in vitro competition assay. The effect of a 1% colloidal oat–containing moisturizer on lactic acid content of the stratum corneum was clinically assessed in subjects with moderate-to-severe dry skin. S. epidermidis gene expression was evaluated by next-generation mRNA sequencing. Short-chain fatty acids were quantified in bacterial culture supernatants.Results: In vitro, colloidal oat increased the growth rate of S. epidermidis vs S. aureus, as well as the metabolism of S. epidermidis. Colloidal oat also significantly increased lactic acid concentrations in supernatants of both strains and decreased pH, consistent with clinical findings that 6-week use of a 1% colloidal oat–containing lotion significantly increased lactic acid on dry skin. Further analyses suggest that colloidal oat alters the gene expression profile of S. epidermidis.Conclusion: Colloidal oat directly affects the growth, metabolism, lactic acid production, and gene expression of skin commensal bacteria, as shown via in vitro studies. The increased production of lactic acid reflects clinical observations with colloidal oat–containing skin moisturizers. Our findings suggest a new mechanism for colloidal oat as a skin prebiotic, which may contribute to improvements in skin and microbiome diversity in various skin conditions, including dry/itchy skin and atopic dermatitis.Keywords: atopic dermatitis, dry skin, colloidal oat, skin barrier function, skin microbiome, skin moisturizer, S. epidermidis